Coronavirus Nsp1: Immune Response Suppression and Protein Expression Inhibition - Yuan, Shuai; Balaji, Shravani; Lomakin, Ivan B.; Xiong, Yong (Frontiers in Microbiology, 2021)
Coronaviruses have brought severe challenges to public health all over the world in the past twenty years. SARS-CoV-2, the causative agent of the COVID-19 pandemic that has led to millions of deaths, belongs to the genus beta-coronavirus. Alpha- and beta-coronaviruses encode a unique protein, non-structural protein 1 (Nsp1), that both suppresses host immune responses and reduces global gene expression levels in the host cells. As a key pathogenicity factor of coronaviruses, Nsp1 redirects the host translation machinery to increase synthesis of viral proteins. Through multiple mechanisms, coronaviruses impede host protein expression through Nsp1, while escaping inhibition to allow the translation of viral RNA. In this review, we discuss current data about suppression of the immune responses and inhibition of protein synthesis induced by coronavirus Nsp1, as well as the prospect of vaccine development targeting Nsp1.